2015
DOI: 10.1136/lupus-2014-000066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corticosteroid use by dose on the risk of developing organ damage over time in systemic lupus erythematosus—the Hopkins Lupus Cohort

Abstract: ObjectivesThe impact of corticosteroids on the risk of organ damage in the context of clinical end points endorsed in some systemic lupus erythematosus (SLE) clinical trials is underexplored.MethodsWe analysed data from the Hopkins Lupus Cohort using Cox proportional hazards models to understand the impact of exposure to different corticosteroid doses on the risk of developing any new organ damage or any new organ damage at the individual organ systems over time.ResultsMean prior prednisone dose, recent diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
102
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(123 citation statements)
references
References 11 publications
5
102
1
4
Order By: Relevance
“…Although they have predictable dose-dependent adverse effects, glucocorticoids continue to be widely used in SLE because of a lack of suitable alternatives. Given emerging evidence of harm associated with the use of glucocorticoids in SLE,7 19 reduction in glucocorticoid dose has been used as a secondary endpoint in clinical trials and recommended as part of a treat-to-target approach 2021 However, the nexus between the beneficial and harmful effects of glucocorticoids in SLE is incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they have predictable dose-dependent adverse effects, glucocorticoids continue to be widely used in SLE because of a lack of suitable alternatives. Given emerging evidence of harm associated with the use of glucocorticoids in SLE,7 19 reduction in glucocorticoid dose has been used as a secondary endpoint in clinical trials and recommended as part of a treat-to-target approach 2021 However, the nexus between the beneficial and harmful effects of glucocorticoids in SLE is incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…They did not report the contribution of disease activity to damage accrual, and disease activity was integrated into multivariate analysis using mean SLEDAI as opposed to the more informative AMS. A recent analysis of over 2000 patients with a mean observed period of 6.2 years in the Hopkins Cohort19 reported a 2.8% increased risk of developing new organ damage for each 1 mg/day of prednisolone. An independent association of glucocorticoid use with damage accrual was also recently reported in the Systemic Lupus International Collaborating Clinics (SLICC) inception cohort, although in that study glucocorticoid use was only recorded as present or absent,24 preventing consideration of dose thresholds to damage accrual.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of steroids is a major goal in the treatment of chronic SLE as evidence is emerging that major damage accumulation results more from steroid therapy than lupus disease activity. 21 The initial dose of prednisolone in the first month of therapy after diagnosis of SLE is predictive of prednisolone doses over the following 11 months. 22 Organ complications secondary to chronic corticosteroid use occur in a dose-dependent manner.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…An increase in the average prednisolone dose by 1 mg/day is estimated to increase the risk of cataracts by 3.8% and osteoporotic fractures by 4.2%. 21 in those with resistant disease. There are several case series of good response that support the use of rituximab.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Al Sawah and colleagues showed that daily prednisone doses of over 7.5 mg increased the risk of developing cataracts, osteoporotic fractures and cardiovascular damage. They estimated that an increase in mean prednisone dose of just 1 mg/day was associated with a 3.8% increased risk of cataracts and 4.2% increase in osteoporotic fractures(10). Using multivariate modeling, chronic prednisone use was one of the factors which predicted the accrual of organ damage in SLE(11).…”
Section: Corticosteroid Therapy In Slementioning
confidence: 99%